Subcapsular hematoma of liver: Not too frequent occurrence and tomographic follow up. - Rodríguez, José L; Piñeyro, Alberto; Cidade, Luis (Cirugía del Uruguay, 1987)
Again presenting a case of subcapsular hematoma of the llver, treated In an expectant manner, with cllnical and tomographlc follow up. Speclal emphasls Is laid on the fact that this conser• vative procedure requires a careful selection of the patients and posslbility of adequate cllnical and paraclinical follow up. The patient should be laparotomized in. the presence of infection elements, peritoneal bleeding or hemobilia.